(untitled) (MAUSAM, 1983)
The frequency of famines and rainfall deficiency is described for the last quarter of the nineteenth century. Historical records suggest that there were 14 famines between the 11th and 17th centuries and another 12 famines in 9O.year period 1769 and 1958, with a sharp increase in number between 1860 and 1908. But, famines did not always coincide with years of drought. Past evidence suggests that many famines were caused by lack of 223 adequate communications. In recent years research has been directed towards development of drought indices. Using an index Bhalme and Mooley (1981) found droughts in 1951, 1965-66,1972 and 1.974. Two years of consecutive drought in 1.965 and 1966 was a rare event. In the second part of this paper we describe .a stochastic prediction technique based on autoregresson for monsoon rainfall. This is a variation of ARIMA, which has been used in econometrics but has an interesting application in Meteorology.